Familial Acute Myeloid Leukaemia with Acquired Pelger-Huët Anomaly and Aneuploidy of C Group. Issue 5836 (11th November 1972) - Kaur, Juginder; Catovsky, D.; Valdimarsson, H.; Jensson, O.; Spiers, A. S. D.
Abstract : All five members of one generation in an Icelandic family were affected by acute myeloid leukaemia or preleukaemia. Two sibs died of acute myeloid leukaemia and another of myelofibrosis associated with leukaemic changes. The other two sibs are alive; one of them (the propositus) has haematological features consistent with preleukaemia; both of them have evidence of an abnormal cytogenetic clone in the bone marrow with 47 chromosomes, an extra chromosome in the C group. The finding of the acquired Pelger-Huët anomaly in the neutrophils of the five affected sibs suggests that a specific genetic cell defect has been transmitted with autosomal dominant characteristics. The presence of immunological deficiencies and an undue susceptibility to oncogenic viruses, as suggested by warts affecting three family members, may have played a part in the pathogenesis of the leukaemic process.